Repeated Interactions Versus Social Ties: Quantifying the Economic Value of Trust, Forgiveness, and Reputation Using a Field Experiment1 - Bapna, Ravi; Qiu, Liangfei; Rice, Sarah (MIS Quarterly, 2017)
The growing importance of online social networks provides fertile ground for researchers seeking to gain a deeper understanding of fundamental constructs of human behavior, such as trust and forgiveness, and their linkage to social ties. Through a field experiment that uses data from the Facebook API to measure social ties that connect our subjects, we separate forward-looking instrumental trust from static intrinsic trust and show that the level of instrumental trust and forgiveness, and the effect of forgiveness on deterring future defections, crucially depend on the strength of social ties. We find that the level of trust under social repeated play is greater than the level of trust under anonymous repeated play, which in turn is greater than the level of trust under anonymous one shot games. We also uncover forgiveness as a key mechanism that facilitates the cooperative equilibrium being more stable in the presence of social ties: If the trading partners are socially connected, the equilibrium is more likely to return to the original cooperative one after small disturbances.